Sosialisasi Bahaya Media Sosial sebagai Modus Perdagangan Orang pada Remaja di Jatinangor - Benazir Bona Pratamawaty; Evie Ariadne Shinta Dewi; Putri Limilia (Lembaga penelitian dan pengabdian kepada masyrakat, 2021)
In the period of January to April 2021, 234 children were found to be the victims of the children trafficking and 60% of them were recruited through the social media. Children and young adults were told that they will be hired as employee and earn sophisticated salary while in fact they were tricked into sexual exploitation. Pandemic and high internet penetration results in increasing internet use for children and young adults. Hence, both children and young adults are prone to the human trafficking practices. Therefore, it is urgent to conduct socialization and education towards children and young adults regarding the high risks of social media use as the recruitment tools for human trafficking perpetrators. This community service aimed to increasing knowledge and rising awareness of the young adults in Jatinangor with regard to the threat of social media as the human trafficking modus of practices. The data collection comprised of online survey before and after the socialization. Because of the pandemic, the socialization took place online or known as Webinar. The webinar was divided into three session which consisted of polling session (pre-test), talks and discussion session, then post-test session. The objectives of this webinar were to socialize, educate, and develop social awareness with regard to the human trafficking threats. The online survey results were analyzed using quantitative descriptive technique. The results indicate that after the webinar the participant succeed in gaining knowledge and understanding of the human trafficking recruitment modus and how the social media used as one of the modus.